Manchester's Workers - Kealey, Gregory S. (Labour / Le Travail, 1984)
The article reviews and comments on "Family Time and Industrial Time. The Relationship Between the Family and Work in a New England Industrial Community," by Tamara K. Hareven, and "The Working Population of Manchester, New Hampshire, 1840-1886," by James P. Hanlan.

Editor's Note = Note du directeur [14, Fall 1984] - Kealey, Gregory S. (Labour / Le Travail, 1984)
Introduces two new sections in the journal on correspondence and debates, and thanks two departing members of the editorial board for their service.

1919: The Canadian Labour Revolt - Kealey, Gregory S. (Labour / Le Travail, 1984)
This essay attempts to place Canadian workers' 1919 militancy in a national and international context. Utilizing freshly compiled strike data and focusing on events outside of Winnipeg, the paper argues that the 1919 revolt was nation-wide and part of the international post-war revolutionary upsurge. The new prominence of women and immigrant workers, reflecting the drive for industrial unionism, is emphasized.

Editor's Note = Note du directeur [13, Spring 1984] - Kealey, Gregory S. (Labour / Le Travail, 1984)
The editor notes that the issue contains papers presented at the 1919 Winnipeg General Strike symposium held at the University of Winnipeg in March 1983. The symposium's organizers, Nolan Reilly and Paul Stevenson, also served as guest editors for the issue. Also notes the change of the French title of the journal to Le Travail to avoid the sexist connotation of Le Travailleur, for which the editor apologized.

Modern Canada, 1930-1980's - Cross, Michael S.; Kealey, Gregory S. (Readings in Canadian social history, 1984)
[This book] is the last of a 5-volume series of readers designed to present an overview of Canada's social history, encompassing such topics as economic development, social structure, protest and violence, social control, work and workers, and the changing role of women. In this volume the editors have commissioned a collection of original essays designed to provide a scholarly response to the vital questions: "Who are we as a people? How did we become what we are?" The extent and influence of foreign ownership in the post-war world is examined by Paul Phillips and Stephen Watson. David Wolfe chronicles the emergence of the welfare state after the war and its recent decline. Michael Behiels explores the ideological tensions among federalist, nationalist, and socialist intellectuals in Quebec and Canada. Ruther Pierson and Marjorie Cohen discuss sexual bias in federal manpower policies in depression, war, and reconstruction. The struggles of labour, management, and government are examined in articles by Wayne Robert and John Bullen, and by Wallace Clement. And the education system as a instrument of social control is the subject of Paul Axelrod's essay. --Publisher's description
Keywords: Aufsatzsammlung; Canada; Canada - Conditions sociales - 20e siècle; Canada - Conditions économiques - 20e siècle; Canada - Histoire - 20e siècle; Canada Conditions sociales; Canada Conditions économiques 1918-1945; Canada Conditions économiques 1945-; Canada Conditions économiques 20e siècle; Canada Economic conditions 1918-1945; Canada Economic conditions 1945-; Canada Economic conditions 20th century; Canada Social conditions; Economic history; Economic, Social, and Cultural History of North America; Economische, sociale en cultuurgeschiedenis van Noord-Amerika; Kanada; Since 1918; Social conditions; Sozialgeschichte 1930-1980; canada; geschiedenis; historical records; historische verslagen; history; social change; social processes; sociale processen; sociale verandering